TINJAUAN HUKUM SANKSI ADAT MBACURIE SAU TERHADAP PERKAWINAN MERTUA DAN MENANTU DESA MATAWIA KEC.WOLOWA KAB. BUTON - Syarifuddin, Muh; Widya Wijaya (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The formulation of the problem proposed is: How is the process of implementing the mbacurie sau customary sanctions in Matawi village and what are the factors that cause the imposition of mbacurie sau customary sanctions. This study uses primary data sources from interviews with informants and field or empirical results and secondary data sources in the form of the 1945 Constitution of the Republic of Indonesia, the Civil Code (KUHPer), Government Regulation Number 9 of 1975 Jo Number 1 of 2019 concerning Marriage, Compilation of Islamic Law (KHI), books, internet articles, legal journals. Data collection methods by interview and field results as well as literature studies in the form of narrative text, namely systematic sequence. Customary law in Matawia Village, particularly the mbacurie sau sanction, is an important instrument in maintaining order and harmony within the indigenous community. In the past, this sanction was applied to various forms of customary violations. However, along with social developments, its application is now more focused on violations related to marriage and actions that oppose decisions or undermine the authority of customary leaders (sara). The implementation process of the mbacurie sau sanction is carried out in a structured manner through several stages, starting from reporting, customary deliberation, monitoring, and ending with a decision in a customary court session. The primary purpose of enforcing this sanction is to strengthen the position of sara as the highest customary authority, ensuring that community members do not act arbitrarily, even though, in modern times, state law is also increasingly considered. The sanctions imposed on violators of customary norms include advice or reprimands, compensation, fines, and the most severe sanction, namely social exclusion or expulsion from the village. The implementation of these sanctions is adjusted based on the type of violation and its impact on the legal order and social balance within the indigenous community. Therefore, the main factor causing the enforcement of the mbacurie sau customary sanction in Matawia Village is the violation of prevailing customary norms and regulations, particularly those related to marriage, the authority of sara, and opposition to customary decisions